"IT WAS NOT A HIT; IT WAS A RISE. » ANALYSIS AND PERSPECTIVES ON THE CHILEAN VIA TO SOCIALISM FROM THE PAGES OF FUERZA NUEVA MAGAZINE (1970-1973) - Morales Aguilera, Francisco Javier (Revista de Historia Social y de las Mentalidades, 2020)
This article investigates the perspective and position of the Spanish nationalist magazine Fuerza Nueva in relation to the Popular Unity government between the years 1970-1973. The analysis of the content was carried out on the basis of an exhaustive review of the almost fifty articles that were published on the Chilean socialist experience in that period. Most of the ideas and opinions expressed in this regard were articulated around a more or less transversal topic that identified this government and its project of structural transformation as an unequivocal case of the expansion of Soviet communism in Latin America. This view, in addition to showing a strong anti-communist stance, would also reveal an attempt to homologate part of the Chilean reality of the time to the context of Spain in the 1930s, in order to make an interconnected reading between both experiences.
Keywords: Spain; Francoist Press; Popular Unity; Communism